Creative Solutions and their Evaluation: Comparing the Effects of Explanation and Argumentation Tasks on Student Reflections - Andiliou, Andria; Murphy, Pricilla Karen (Frontline Learning Research, 2014)
Creative problem solving which results in novel and effective ideas or products is most advanced when learners can analyze, evaluate, and refine their ideas to improve creative solutions. The purpose of this investigation was to examine creative problem solving performance in undergraduate students and determine the tasks that support critical self-evaluations of creative solutions by comparing alternative types of reflective tasks. Participants (n = 103) first provided demographic information and responded to individual difference measures (i.e., divergent thinking, need for cognition, and beliefs about creative outcomes) and then read a problem scenario in which they assumed the role of a high school teacher who was asked to design a creative college preparatory course. Following, participants completed either an explanation reflective task or an argument based reflective task. Finally, participants evaluated their proposed course by rating it on characteristics that describe the originality and effectiveness of creative solutions. Findings confirmed the role of divergent thinking as a positive predictor of the originality of a creative solution, whereas, need for cognition, and academic major were positive predictors of the effectiveness of a creative solution. Participants rated their creative solutions differentially depending on their beliefs and the type of reflective task. Those whose beliefs aligned better with conceptualizations of creative outcomes assessed more positively the originality and effectiveness of their solution. The findings indicate that the argumentation task could potentially promote reflective and critical thinking about a creative solution as participants who completed the argumentation task evaluated their solution more conservatively.